T-cell engagers: model interrogation as a tool to quantify the interplay of relative affinity and target expression on trimer formation - Lai, Massimo; Pichardo-Almarza, Cesar; Verma, Meghna; Shahinuzzaman, Md; Zhu, Xu; Kimko, Holly (Frontiers in Pharmacology, 2024)
T-cell engagers (TCEs) represent a promising therapeutic strategy for various cancers and autoimmune disorders. These bispecific antibodies act as bridges, connecting T-cell receptors (TCRs) to target cells (either malignant or autoreactive) via interactions with specific tumourassociated antigens (TAAs) or autoantigens to form trimeric synapses, or trimers, that co-localise T-cells with target cells and stimulate their cytotoxic function. Bispecific TCEs are expected to exhibit a bell-shaped dose-response curve, with a defined optimal TCE exposure for maximizing trimer formation. The shape of the dose-response is determined by a non-trivial interplay of binding affinities, exposure and antigens expression levels. Furthermore, excessively low binding to the TCR may reduce efficacy, but mitigate risk of over-stimulating cytokine secretion or induce effector cell exhaustion. These inevitable trade-off highlights the importance of quantitatively understanding the relationship between TCE concentration, target expression, binding affinities, and trimer formation. We utilized a mechanistic target engagement model to show that, if the TCE design parameters are close to the recommended ranges found in the literature, relative affinities for TCR, TAA and target expression levels have qualitatively different, but predictable, effects on the resulting dose-response curve: higher expression levels shift the curve upwards, higher antigen affinity shifts the curve to the left, and higher TCR affinity shifts the curve upwards and to the left.